E-bike as a technological innovation system in China: transition to the stage of institutionalized certainty? - Zuev, D. (Applied Mobilities, 2020)
The paper aims at discussing the current stage of development of e-bike as a technological innovation system in China. The article looks at the evolution of the e-bike mobility system from spontaneous emergence through fractional restrictions to the current stage with signs of institutionalized certainty. It is argued that the current transitional dynamics are characterized by the processes of standardization, wider incorporation of e-bike in bike-sharing schemes, regulation of charging infrastructure and “smartification” of e-bike mobility. These processes are likely to have influence on practices of e-bike mobility: the shifting meanings, the relevance of new skills and competences and transforming sociomaterial arrangements. The current transition dynamics is marked by the rising global significance of urban micro-mobility and the increasing role of electric two-wheelers oriented at fueling mobility as a service.